Hubungan pemberian makanan pendamping air susu ibu (MP-ASI) dini dengan kejadian diare pada bayi usia 0-6 bulan di klinik Pratama Evi - Azzahra, Nasywa Firja; Sari , Delia Permata; Sapitri , Anggiani; Simamora , Apriyanti; Tondang, Kesya Nirina; Paninsari, Debora (Journal of Pharmaceutical and Sciences, 2025)
Background: The global coverage of exclusive breastfeeding remains low (44%). The situation in Indonesia, particularly in North Sumatra, is concerning, where 68.4% of children under two years receive complementary feeding (CF) too early. This practice may increase the risk of diarrhea due to the immaturity of the infant’s gastrointestinal tract. Preliminary findings at Evi Primary Clinic showed that 17 out of 20 infants under six months experienced diarrhea, along with evidence of early CF practices. Objective: This study aimed to analyze the association between early complementary feeding and the incidence of diarrhea among infants aged 0–6 months at Evi Primary Clinic. Methods: An observational analytic study with a cross-sectional design was conducted. A total sampling technique was applied to 35 mothers with infants aged 0–6 months. Data were collected using questionnaires and analyzed using the Chi-Square test. Results: A total of 19 infants (54.3%) received early complementary feeding, and 18 infants (51.4%) experienced diarrhea. Bivariate analysis revealed that 15 out of 19 infants (42.8%) who received early complementary feeding suffered from diarrhea. The statistical test showed a p-value of 0.001 (α<0.05). Conclusion: There is a statistically significant association between early complementary feeding and the incidence of diarrhea among infants aged 0–6 months at Evi Primary Clinic. Therefore, education on the appropriate timing of complementary feeding is essential to prevent diarrhea in infants.